2021
DOI: 10.1177/23259582211062754
|View full text |Cite
|
Sign up to set email alerts
|

Adolescents and Young Adults Knowledge, Adherence and Experiences While on Antiretroviral Therapy in a Tertiary Hospital in Lagos, Nigeria: A Mixed-Method Study

Abstract: In Nigeria, there is a paucity of data on knowledge and experiences of adolescents and young adults (AYAs) with HIV and ART, as well as their challenges maintaining optimal adherence. A mixed-method study was carried out between August and September 2018 among AYAs attending Lagos University Teaching Hospital, Nigeria. Data collection was via AYAs' hospital records, standardized questionnaires, and in-depth interviews (IDIs). The 4-day ACTG tool was used to measure adherence. Collected data were analyzed descr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 18 publications
(38 reference statements)
0
4
0
Order By: Relevance
“…These studies consistently reported a positive relationship between higher education levels and improved PrEP adherence. Conversely, some studies indicated that individuals with lower education levels, including those with limited HIV knowledge, exhibited poorer PrEP adherence [ 17 , 25 ]. These findings underscore the potential impact of education on PrEP adherence and emphasize the importance of considering individuals’ educational backgrounds and HIV knowledge in understanding adherence behaviors.…”
Section: Discussionmentioning
confidence: 99%
“…These studies consistently reported a positive relationship between higher education levels and improved PrEP adherence. Conversely, some studies indicated that individuals with lower education levels, including those with limited HIV knowledge, exhibited poorer PrEP adherence [ 17 , 25 ]. These findings underscore the potential impact of education on PrEP adherence and emphasize the importance of considering individuals’ educational backgrounds and HIV knowledge in understanding adherence behaviors.…”
Section: Discussionmentioning
confidence: 99%
“…Women have been known to have better health seeking behaviour [44,45] and better adherence to treatment than men [46] which would consequently lead to improved viral suppression [47]. Similarly, adults have been shown to be more likely to be adherent to ART compared to adolescents and young persons [48][49][50], while MMD and community-based ART models are proven strategies for improving ART adherence [22,23,32]. Targeted program interventions to these affected socio-demographics may enhance viral suppression.…”
Section: Plos Onementioning
confidence: 99%
“…Regular education and sensitization equipped respondents with adequate information about the importance of adherence to antiretroviral treatment. In relation, a study carried out in Nigeria found that adolescents who had routine education and sensitization about ART were more adherent to ART as compared to those who were not health-educated [35,36]. This was because both studies were carried out in rural settings where the social demographic characteristics of the respondents were similar.…”
Section: Drug-related Factors Associated Withmentioning
confidence: 99%